Penggunaan buklet dalam meningkatkan literasi perilaku hidup bersih dan sehat kader posyandu - Yuliani Yuliani; Agus Rusmana; Ute Lies Siti Khadijah (Faculty of Communication, Padjadjaran University, 2023)
This study was conducted to determine the effective booklet design and its use in enhancing the literacy of PHBS cadres at Posyandu in Jatinangor Sub-district. The method used is qualitative with an action research approach. The booklet creation followed four stages based on the action research theory: planning, implementing, observing, and reflecting. The informants in this study consisted of eight cadres from two community health posts in Jatinangor Sub-district. These eight cadres are from Posyandu Nuri 3 (Cikeruh Village, RW 03) and Posyandu Nuri 4 (Cikeruh Village, RW 04). Data were collected through interviews, observations, FGDs, and literature studies. The results of this study indicated that the criteria for an effective booklet include being user-oriented, credible, easily understandable, and visually appealing. The information sources used in the booklet come from trusted sources such as the Jatinangor Health Center, the Indonesian Ministry of Health, and health journals. The language used in the booklet is clear, straightforward, and simple in Indonesian, making it easily understandable for the cadres. The booklet has a colorful design and supporting images to make it more appealing. The booklet aims to enhance the cadres' knowledge of self-care, caring for others, preventing diseases, and persuading the community to apply these principles in daily activities. In conclusion, the booklet can be used to improve the PHBS literacy of Posyandu cadres.